Inventario vial de la vía Loja Malacatos Vilcabamba como aporte al observatorio de Ingeniería de Tráfico - Granda Elizalde, Andrés Abel (2018)
Abstract:Due to the lack of information in the road network in the Province of Loja, we have opted for techniques, mechanisms and systematization for the identification and collection of data obtained in the road field. With this road project, it is possible to establish detailed information on hydraulic construction works such as culverts and bridges, this is because over time the initial design conditions are changing; zones of geological faults, since these generate problems and alter the normal traffic circulation. The details of the road infrastructure are obtained through the execution of specific surveys of data in the field that are achieved through routes in the road network. With the information collected and with the help of computer tools such as the Geographic Information System, an updated database and digital maps are created to plan and improve the road infrastructure. This initiative will provide technical information as a result, which will serve as input to the Traffic Engineering Observatory and institutions that require such information for the development of road improvement plans.